SOSIALISASI PENCEGAHAN PELECEHAN SEKSUAL PADA ANAK DAN WANITA BAGI IMIGRAN DI COMMUNITY HOUSE OF IOM PUSPA AGRO SIDOARJO - Afifah, Wiwik; Ayu Atika, Nisfu; Pangeran Jaya, Alifsyah; Khartika Suryanis, Ammalia; Lailatul Maghfiroh, Anik; Dewi Pratiwi, Nita; Fikri, Sultoni (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2024)
Students of the Faculty of Law, University of August 17, 1945 Surabaya carried out the initiative of Discussion Activities at the Community House of IOM Puspa Agro Sidoarjo. The activity aims to provide a forum for knowledge with the theme used as material for discussion, namely Prevention of Sexual Abuse of Children and Women in Indonesia. This discussion also provides solutions to the problems faced by partners, especially the lack of knowledge of immigrants about aspects of preventing sexual violence in Indonesia, including the definition of abuse, forms of abuse, the impact and prevention of sexual abuse on children and women, protection and factors. The method of implementing this service program involves initial preparation, implementation of material counseling, discussion related to the material, as well as evaluation and report making. A positive response was received from the partners, who actively provided feedback during the discussion. The results of this discussion provide benefits for refugee immigrants, of course they get new knowledge and insights about sexual abuse in children and women and can implement it in their daily lives. Thus, this program successfully achieved its objectives by increasing the understanding of immigrants in the Community House of IOM Puspa Agro Sidoarjo regarding the Prevention of Sexual Abuse of Children and Women.